4 - Can It be Achieved? Partnering Towards Improving Livelihoods in the Ganspan Settlement, Northern Cape Province, South Africa - Norris, D.; Van Zyl, E.C.; Hashe, W.T.; Mafuma, M.S.; Senyolo, M. P.; Mngomezulu, S. P.; Enserink, D.; Ngambi, J.W.; Mbajiorgu, C.A. (Africa Development, 2021)
The Agricultural Research for Development (ARD) approach was used to determine the livelihood strategies of the Ganspan community; the current socio-economic dynamics and how they impact on livelihoods; the vision for the future; and to develop an initial road map for achieving better livelihoods. Eighty out of 210 households were sampled to determine the livelihood typology of the settlement. Participatory rural appraisal tools were used to explore stakeholders’ perceptions of the current problems/opportunities and the possible solutions. Only 3 per cent of households are solely dependent on agriculture whereas the majority (76%) derive livelihood from non-agricultural activities. The rest of the households derive their livelihoods from both agricultural and non-agricultural activities. Agriculture has a modest contribution to household income compared to social grants and employment. Generally, the community is economically depressed. Developmental strategies were identified, screened and prioritised. Collaboration and joint action by various stakeholders is essential for the sustainable development of the settlement. The establishment of an innovation platform with representatives of all relevant stakeholders is strongly recommended in order to jointly implement integrated and inter-institutional development action plans.